2003
DOI: 10.1007/s00122-003-1228-x
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and molecular characterization of a rice glutelin allele for the GluA-1 gene

Abstract: The rice ( Oryza sativa L.) mutant of glu4a, lacking the glutelin alpha-2 subunit while the alpha-1 subunit increased (alpha-1H/alpha-2L), was used in this study. Two-dimensional electrophoresis analysis revealed that the mutant lacked the polypeptide pI6.71/alpha-2 encoded by glu4 while forming a new polypeptide of pI6.50/alpha-1. Experiments were conducted to identify the relationships between the mutated polypeptides of the mutant and to illustrate the mutation mechanism of the allele. Peptide mapping and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…An extensive analysis of the complete rice genome sequence indicates that there are at least 11 glutelin genes ( Katsube-Tanaka et al , 2004 ). However, only GluA-1, GluB-4, and GluB-5 have been conclusively associated with their corresponding genes ( Kusaba et al , 2003 ; Qu et al , 2003 ; Morita et al , 2007 ).…”
Section: Discussionmentioning
confidence: 97%
“…An extensive analysis of the complete rice genome sequence indicates that there are at least 11 glutelin genes ( Katsube-Tanaka et al , 2004 ). However, only GluA-1, GluB-4, and GluB-5 have been conclusively associated with their corresponding genes ( Kusaba et al , 2003 ; Qu et al , 2003 ; Morita et al , 2007 ).…”
Section: Discussionmentioning
confidence: 97%
“…AGPS2 could be coordinated with starch accumulation in the developing rice seed [29]. Moreover, two glu4a genes (JreChr03G12610 and JreChr03G12612) involved in seed glutelin quality (eating quality) [30], and one th1 gene (JreChr03G12627) related to seed weight per panicle in rice [31], were found within the candidate selected region (Chr3: 42.5-42.7 Mb). In addition to genes related to seed traits, we found two genes coding nitrilase with Pfam "PF00795" (carbon-nitrogen hydrolase) within a selected region (Chr13: 20.9-21.3 Mb) identified by two selective approaches (Additional file 7: Table S6).…”
Section: Signatures Of Selection In Walnut Genomesmentioning
confidence: 99%
“…Qu et al. () reported that the mutant lacked the polypeptide pI6.71/α‐2 encoded by GLU4 gene, while forming a new polypeptide (pI6.50/α‐1), which was encoded by the GLU4a gene. Using IEF and two‐dimensional electrophoresis analysis, Wen and Luthe () and Qu et al.…”
Section: Discussionmentioning
confidence: 99%